Peran Integrated Marketing Communication Terhadap Minat Kunjungan Wisatawan Beach Forest Kabupaten Situbondo - Putri Nur Harizah; Juariyah (Universitas Gunadarma, 2026)
This study aims to analyze the role of Integrated Marketing Communication (IMC) in building tourist interest in Beach Forest Situbondo and identify barriers to its implementation. The study used a qualitative descriptive approach and was conducted at Beach Forest Situbondo, Situbondo Regency, East Java. The results showed that IMC was implemented through advertising, sales promotions, public relations, digital marketing, direct marketing, and word-of-mouth. Digital marketing through TikTok was the most prominent element in building tourist interest in the destination through engaging visual content. Sales promotions, collaboration with communities and influencers, direct marketing through WhatsApp Business and word-of-mouth communication complemented each other in building tourist interest, destination image, and trust. However, the implementation of IMC still faces obstacles such as limited digital promotion costs and a mismatch between promotional messages and field conditions, particularly regarding cleanliness. Therefore, a more integrated, consistent, and sustainable marketing communication strategy is needed to strengthen the destination's image and sustainable marketing communication.